Array comparative genomic hybridization in global developmental delay - Shevell, M.I.; Bejjani, B.A.; Srour, M.; Rorem, E.A.; Hall, N.; Shaffer, L.G. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2008)
Objective: Array‐based comparative genomic hybridization (array CGH) is an emerging technology that allows for the genome‐wide detection of DNA copy number changes (CNC) such as deletions or duplications. In this study, array‐based CGH was applied to a consecutive series of children with previously undiagnosed non‐syndromal global developmental delay (GDD) to assess potential etiologic yield. Methods: The children in this study were drawn from a previously reported consecutive series of children with well‐defined GDD. Almost all subjects had undergone prior karyotyping and neuroimaging studies with non‐diagnostic results. Array‐based CGH was undertaken using the SignatureChip® (1887 BACs representing 622 loci) with abnormalities verified by subsequent FISH analysis and testing of parents to distinguish between pathogenic and familial non‐pathogenic variants. Results: On CGH analysis in our study, 6 of 94 children (6.4%) had a causally related pathogenic CNC. Three were sub‐telomeric in location. An analysis of a variety of clinical factors revealed that only the presence of minor dysmorphic features (<3) was predictive of etiologic yield on CGH analysis (4/26 vs. 2/68, P = 0.05). Severity of delay was not found to be predictive. Interpretation: In children with non‐syndromal GDD, array‐based CGH has an etiologic yield of 6.4%. This suggests that this emerging technology may be of diagnostic value when applied subsequent to detailed history, physical examination, and targeted laboratory testing. Array CGH may merit consideration as a first‐tier test in the context of a child with unexplained GDD. © 2008 Wiley‐Liss, Inc.